Pessoas que habitam as ruas em Fortaleza nos circuitos da vulnerabilidade e exclusão: identidades em construção nas trajetórias e percursos - Langa, Ercílio Neves Brandão (2012)
This dissertation supports an effort for the understanding of the universe populated by street dwellers in Fortaleza by means of a two-year research encompassing a process of redefinitions of the object from interpretations arising from the field. The work includes as its investigative axis the trajectories of people inhabiting the streets of Fortaleza focusing on processes of disaffiliation and new affiliation, the “habitus” that imprint the “street dweller”, precarious exclusions and inclusions, discriminations, prejudices, conceptions and values adopted by these characters inhabiting the streets and, especially, conceptions and attitudes in face of the HIV/AIDS. The main point of the analysis ended up focusing upon the construction of identity-based processes found at the trajectories of the streets dwellers. To enter this universe required the buildup of a “street ethnography” that was carried up in the Gentilandia Square and four Homes in a period of 18 months trying to follow the routes of constituting characters of the investigation field. The ethnographic work carried out from a special place allowed the researcher to feel the street dweller’s condition on “his very skin” considering that he was in the course of the research confounded with those subjects whom he was trying to understand. The investigative process in the streets, clerically constructed, led the researcher to approach theoretical support based on a permanent biographical search which allowed amplifying and reconfiguring theorizations in accordance with his own empirical ideas. Castel’s (1997) concept of social de-affiliation was used here to characterize the individual’s double alienation from the labor market on the one hand and family’s ties on the other, and Goffman’s (1988) concept of stigma which becomes evident as a classification strategy for individuals within daily interactions, emphasizing difference in relation to features that have been considered normal. Bauman’s (2005) idea of human waste that nominates human beings, plagued by excesses and redundancies from the modern age, and who live at the brink of inescapable situations, and Hall’s (2006) deconstructivist perspective of identities are other theoretical approaches used by this work. Indeed, street dwellers, that experience processes of exclusion and are subjected to risks going from infancy up to adolescence and adult age, reveal through their lives poverty-ridden situations, negation of rights and family ruptures. They start working very early in life in order to help feed the family by doing odd jobs, trading illicit merchandise, trafficking drugs, perpetrating assaults, besides engaging in other urban economic activities in poor areas of the city. By their urban mobility and experience of life, they develop forms and mechanisms of precarious inclusions such as working as collectors of solid wastes, keeping guard of cars in the streets, taking temporary jobs in the construction of buildings and houses, practicing illicit acts and resorting to shelters and homes.